Pengukuran Kinerja Keuangan Bank Pembiayaan Rakyat Syariah di Indonesia Melalui Pendekatan Shariah Conformity and Profitability (SCnP) Model Pada Periode 2018-2020 - Ahmad Fatoni; Najmudin Najmudin; Kurnia Dwi Sari Utami (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2021)
Measurement of Islamic banking financial performance using conventional methods shows unsatisfactory results. This method tends to prioritize profit and override sharia compliance. This study aims to measure the financial performance of 16 selected Sharia Rural Banks in Indonesia during the 2018-2020 period. Meanwhile, the measuring instrument used is Shariah Conformity and Profitability (SCnP). The results showed that there were only 11 Sharia Rural Banks that were included in quadrant 1 meaning that the bank was performing well with a high level of sharia compliance and high profitability. There are 5 Sharia Rural Banks  that are included in quadrant 2, namely banks that perform quite well with high levels of sharia compliance and low profitability